Factors Influencing Graft Function following MPFL Reconstruction: A Dynamic Simulation Study - Tanaka, Miho J.; Cosgarea, Andrew J.; Forman, Jared M.; Elias, John J. (The Journal of Knee Surgery, 2020)
Medial patellofemoral ligament (MPFL) reconstruction is currently the primary surgical procedure for treating recurrent lateral patellar instability. The understanding of graft function has largely been based on studies performed with normal knees. The current study was performed to characterize graft function following MPFL reconstruction, focusing on the influence of pathologic anatomy on graft tension, variations with knee flexion, and the influence on patellar tracking. Knee squatting was simulated with 15 multibody dynamic simulation models representing knees being treated for recurrent lateral patellar instability. Squatting was simulated in a preoperative condition and following MPFL reconstruction with a hamstrings tendon graft set to allow 0.5 quadrants of lateral patellar translation with the knee at 30 degrees of flexion. Linear regressions were performed to relate maximum tension in the graft to parameters of knee anatomy. Repeated measures comparisons evaluated variations in patellar tracking at 5-degree increments of knee flexion. Maximum graft tension was significantly correlated with a parameter characterizing lateral position of the tibial tuberosity (maximum lateral tibial tuberosity to posterior cruciate ligament attachment distance, r2 = 0.73, p < 0.001). No significant correlations were identified for parameters related to trochlear dysplasia (lateral trochlear inclination) or patella alta (Caton–Deschamps index and patellotrochlear index). Graft tension peaked at low flexion angles and was minimal by 30 degrees of flexion. MPFL reconstruction decreased lateral patellar shift (bisect offset index) compared with preoperative tracking at all flexion angles from 0 to 50 degrees of flexion, except 45 degrees. At 0 degrees, the average bisect offset index decreased from 0.81 for the preoperative condition to 0.71. The results indicate that tension within an MPFL graft increases with the lateral position of the tibial tuberosity. The graft tension peaks at low flexion angles and decreases lateral patellar maltracking. The factors that influence graft function following MPFL reconstruction need to be understood to limit patellar maltracking without overloading the graft or over constraining the patella.
Keywords: patellar instability; MPFL reconstruction; patellar tracking; computational simulation